2017
DOI: 10.1021/acs.jafc.7b01969
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Biological Evaluation of Phenolic Compounds from a Traditional North American Confectionery, Maple Sugar

Abstract: Maple sap, collected from the sugar maple (Acer saccharum) tree, is boiled to produce the popular plant-derived sweetener, maple syrup, which can then be further evaporated to yield a traditional North American confectionery, maple sugar. Although maple sap and maple syrup have been previously studied, the phytochemical constituents of maple sugar are unknown. Herein, 30 phenolic compounds, 1-30, primarily lignans, were isolated and identified (by HRESIMS and NMR) from maple sugar. The isolates included the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…The identified compounds are summarized in Table . From results presented in Table and Figure a, indicate that phenolic acids and lignans were the major polyphenols present in maple syrup, which were also previously reported in the literature (Liu et al, ; St‐Pierre et al, ). All three syrup samples were determined to contain 17 compounds in common; however, four additional phenolic compounds (Peaks 1, 4, 5, and 7) were identified in MS + RBX (Figure c and Table ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The identified compounds are summarized in Table . From results presented in Table and Figure a, indicate that phenolic acids and lignans were the major polyphenols present in maple syrup, which were also previously reported in the literature (Liu et al, ; St‐Pierre et al, ). All three syrup samples were determined to contain 17 compounds in common; however, four additional phenolic compounds (Peaks 1, 4, 5, and 7) were identified in MS + RBX (Figure c and Table ).…”
Section: Resultssupporting
confidence: 85%
“…highlights the ESI (−) chromatogram of ethyl acetate extracted maple syrup (MS, control; Figure 2a), syrup with SBX (MS + SBX; Figure 2b) and with red maple bark extract (MS + RBX, Figure 2c). Polyphenolic compounds were identified based on their mass spectra and HPLC (UV-vis at 270 nm) results, and compared with the available mass spectra data reported in literature on maple products(Geoffroy, Meda, et al, 2017;Liu, Rose, DaSilva, Johnson, & Seeram, 2017;St-Pierre et al, 2014). The identified compounds are summarized in…”
mentioning
confidence: 99%
“…38 Maple sugar was found to contain 30 phenolic compounds that were primarily lignins. 39 Agave was characterized for total phenolic content and antioxidant activity, and non-polar constituents were identified using gas chromatography with mass spectroscopy. 40 The agave characterisation showed higher antioxidant activity in the methanol extract, although no phenolic components were identified in this extract.…”
Section: Characterization Of Phenolic Compounds By Hplcmentioning
confidence: 99%
“…While most studies on vacuum technology focused on sap yield and composition, to our knowledge, no studies have ever reported the impact of this new level of vacuum (25 InHg and more) on maple syrup constituents other than color grade [6]. Recently, polyphenols were reported to provide functional properties such as antioxidant as well as antimicrobial activity to maple syrup and its derivatives [16, 17, 18]. Therefore, it is of interest to investigate the impact of high vacuum sap collection on the value-added compounds of maple syrup.…”
Section: Introductionmentioning
confidence: 99%